A catalog of the Milichiidae of Chile (Diptera: Carnoidea) - González, Christian R.; Mello, Ramon Luciano; Elgueta, Mario; Amorim, Dalton De Souza (Zootaxa, 2025)
An updated catalog of the Milichiidae of Chile is provided. We present all valid names and synonyms for the 12 species and four genera distributed in the country, including information about name, author, year of publication, page number, type species, type depository, type locality, and references. Milichiella Giglio-Tos is the most species-rich genus in Chile, with nine species. The geographical distribution of the different species was compiled from bibliographic data and revised collections.